COVID-19 associated mucormycosis: A bibliometric analysis of Indian research based on Scopus - Dayal, Devi; Gupta, Brij Mohan; Bansal, Jivesh; Singh, Yogendra (Iberoamerican Journal of Science Measurement and Communication, 2023)
Objective. Invasive fungal infections, specifically mucormycosis, showed a massive surge during the COVID-19 pandemic, forcing the global medical fraternity to research this highly fatal co-infection. India has contributed significantly to COVID-19-associated mucormycosis (CAM) research, but a bibliometric analysis of this research topic is scarce. Using established bibliometric methods, we aimed to provide the yield and impact of CAM research in India. Design/Methodology/Approach. The publication data on CAM was extracted from Scopus. Data was analyzed using quality indices such as citations per paper (CPP), relative citation index (RCI), and total linkage strength (TLS). Results/Discussion. India contributed 640 (61.2%) to 1045 global publications on CAM research involving 548 authors from 247 organizations. Only 62 (9.8%) and 96 (15.0%) publications were funded and collaborative. The CAM research was focused on clinical features (36.5%), complications (21.7%), risk factors (19.2%), epidemiology (12.3%), diagnostics & imaging (6.8%), treatment outcomes (4.5%), prognosis (3.4%) and pathophysiology (3.1%). The average CPP of Indian publications was 7.8 compared to 28.2 CPP in France, 17.8 CPP in the USA, 8.7 CPP in Saudi Arabia, 8.3 CPP in Bangladesh, and 8.1 CPP in Iran. The major collaborations were with the USA, Bangladesh, Saudi Arabia, the UK, Pakistan, Malaysia, and UAE. The most productive organizations were PGIMER-Chandigarh (n=47), AIIMS-New Delhi (n=44), and AIIIMS-Jodhpur (n=17), whereas the most impactful organizations were SMS Medical College, Jaipur, SGPGIMS, Lucknow and BJ Medical College, Ahmedabad. The most productive authors were A. Chakrabarti, V. Muthu, and R. Agarwal, and the most impactful were I.S. Sehgal, R. Agarwal, and V. Muthu. The most preferred journals were the Indian Journal of Ophthalmology, the Indian Journal of Otolaryngology and Head & Neck Surgery, and BMJ Case Reports. Conclusions. Even though India is the topmost contributor to global CAM research, the quality of its publications is lower than those from France and the USA. The CAM research is largely non-funded. There is a need to improve international collaboration and increase focus on pathophysiology, epidemiology, and pediatric aspects. This may lead to an improved understanding of CAM and increase survival in affected patients.